The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1806-9126-rbef-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Teorias de gauge a la Utiyama

Abstract: Resumo Revisamos a construção da teoria de gauge para os grupos de Lie semi-simples realizada por Utiyama em seu trabalho “Interpretação da Interação por Invariância Teórica”[1]. Mostramos que para manter a invariância de um sistema de campos ϕ A ( x ) sob um grupo de transformações a n parâmetros ϵ a ( x ) dependentes do ponto x μ é necessário introduzir um novo campo A μ a ( x ). Este campo auxiliar interage com ϕ como manifesto pela derivada covariante ∇ μ ϕ A. Determinamos a lei de tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Besides the ordinary four-potential m A x ( ), a scalar field B x ( ) is introduced. Our proposal keeps the minimal coupling prescription suggested in the seminal works by Weyl [58,59], introduced more generally by Yang and Mills [3,4], and formalized by Utiyama [6]-see also [16]. This means that the gauge potential A μ appears in the definition of the (gauge) covariant derivative ∇ μ ∼ ∂ μ + A μ whereas the scalar field B does not.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Besides the ordinary four-potential m A x ( ), a scalar field B x ( ) is introduced. Our proposal keeps the minimal coupling prescription suggested in the seminal works by Weyl [58,59], introduced more generally by Yang and Mills [3,4], and formalized by Utiyama [6]-see also [16]. This means that the gauge potential A μ appears in the definition of the (gauge) covariant derivative ∇ μ ∼ ∂ μ + A μ whereas the scalar field B does not.…”
Section: Introductionmentioning
confidence: 90%
“…However, Yang-Mills' proposal would not predict a massive m A a , which meant that SU(2) symmetry could not alone account for the weak-field interaction. Actually, the massless character of m A a within gauge theory was proved rigorously by Utiyama [6,16]. He showed that any term of the type…”
Section: Introductionmentioning
confidence: 99%
“…Porém, como era bem sabido por Pauli [8], as partículas intermediadoras dessa interação associada a simetria de isospin local são não massivas, contradizendo o fato da interação forte ser descrita por uma interação de curto alcance e partículas massivas. Paralelamente ao trabalho de Yang-Mills, Utiyama estabelece um cojunto de diretrizes para construir uma teoria de gauge para todos os grupos de Lie semi-simples e inclui também no estudo, a relação entre a gravitação na formulação de tetradas e o eletromagnetismo via conexão [9,10]. Nos dias atuais, o caráter geométrico das interações fundamentais ainda é explorado [11,12].…”
Section: Conceitos Preliminaresunclassified